Characterisation and Design of Direct Numerical Simulations of Turbulent Statistically Planar Flames - Andrej Sternin; Daniel Martinez; Daniel Sternin; Oskar Haidn; Martin Tajmar (Aerospace, 2022)
This work aims to provide support for the design of reliable DNSs for statistically planar flames. Improved simulation design strategies are developed. Therefore, design criteria for the simulative domain are discussed. The gained mathematical relations for all of the relevant physical quantities were channelled into a deterministic calculation strategy for mesh features. To choose design parameter values within the mathematical formulations, guidelines were formulated. For less controllable variables, namely the viscosity and Prandtl number, a measurement technique was developed. A new determination strategy to determine characteristic points within the flame front was conducted. In order to present and compare cases with different Prandtl numbers, normalisation of the x-axis of the regime diagram was suggested.